KELAPA DALAM BUDAYA BALI SERTA UPAYA PELESTARIANNYA - Adiputra, Nyoman; Wardi, I Nyoman (Bumi Lestari; Vol 15 No 1 (2015), 2016)
The coconut has a meaningful role in Balinese live. Economically, the coconut is becoming one of the commodity of Bali. The coconut products such as young and old leaves, flower, young and old fruits and the coconut stems, all of them used by the Balinese. Coconut is considered as food stuff, building materials, and for handycrafts. This article reports the cultural classification of coconut, based on Balinese way of looking. At least there are 12 kinds of coconut, namely: 1) nyuh bulan, 2) nyuh udang, 3) nyuh gading, 4) nyuh gadang, 5) nyuh sudamala, 6) nyuh bojog, 7) nyuh surya, 8) nyuh rangda, 9) nyuh be julit, 10) nyuh bongol, 11) nyuh mulung, and 12) nyuh harum. The intended coconuts are used mainly for religious ceremony. The aim of this article is to desiminate the intended information for it’s conservation and preservation. By knowing that, as a Balinese, hopefully, that every body fully concerned in the preservation program of coconut until forever.
Keywords: coconut, Balinese culture ,concerned, preservation and conservation